Computer‐Aided Process and Plant Development. A Review of Common Software Tools and Methods and Comparison against an Integrated Collaborative Approach1. Issue 1 (8th December 2015) - Merchan, Victor Alejandro; Esche, Erik; Fillinger, Sandra; Tolksdorf, Gregor; Wozny, Günter
Abstract: In process systems engineering models are used for many applications, e.g., process simulation, optimization or control. Various types of models such as shortcut or rigorous models exist. An exchange and reuse thereof is highly desirable, but seldom performed. This article focuses on current approaches for developing and solving process models in specific instances for different applications. A close look will be made at the state of the art in modeling, simulation, and optimization software. Requirements for future software developments are derived to reduce the development and synthesis costs for new chemical engineering processes. The web‐based modeling, simulation, and optimization environment MOSAIC is taken as an example to highlight current developments towards collaborative computer‐aided engineering work. Abstract : The heterogeneity of model and data sources represents a major bottleneck for the efficient application of model‐based methods in process development tasks. This paper gives a close look at the state of the art in modeling software and takes the web‐based environment MOSAIC as an example to highlight current developments towards collaborative computer‐aided engineering work.